Multi-faceted reactivity of N-fluorobenzenesulfonimide (NFSI) under mechanochemical conditions: fluorination, fluorodemethylation, sulfonylation, and amidation reactions - Hernández, José G.; Ardila-Fierro, Karen J.; Barišić, Dajana; Geneste, Hervé (Beilstein Journal of Organic Chemistry, 2022)
In the search for versatile reagents compatible with mechanochemical techniques, in this work we studied the reactivity of N-fluorobenzenesulfonimide (NFSI) by ball milling. We corroborated that, by mechanochemistry, NFSI can engage in a variety of reactions such as fluorinations, fluorodemethylations, sulfonylations, and amidations. In comparison to the protocols reported in solution, the mechanochemical reactions were accomplished in the absence of solvents, in short reaction times, and in yields comparable to or higher than their solvent-based counterparts.
Keywords: amidation; ball mill; fluorination; in situ monitoring; mechanochemistry; NFSI; Raman monitoring; sulfonylation